1996
DOI: 10.1183/09031936.96.09010146
|View full text |Cite
|
Sign up to set email alerts
|

Snoring: analysis, measurement, clinical implications and applications

Abstract: S Sn no or ri in ng g: : a an na al ly ys si is s, , m me ea as su ur re em me en nt t, , c cl li in ni ic ca al l i im mp pl li ic ca at ti io on ns s a an nd d a ap pp pl li ic ca at ti io on ns s F. Dalmasso, R. Prota Snoring: analysis, measurement, clinical implications and applications. F. Dalmasso, R. Prota. © ERS Journals Ltd. 1996. ABSTRACT: Snoring was described in literature even before medicine. Common definitions do not consider acoustic measurements of snoring. In this paper we discuss the main p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 49 publications
1
105
0
3
Order By: Relevance
“…14,15,28 An important problem in dealing with objective respiratory sounds is the comparison of the data of various investigators and correct interpretation. 50 This study shows that a snore detection system can provide an objective quantitative measure for whole-night snore patterns. Further studies are needed both to reinforce our findings by recruiting subjects from primary care clinics and by validating this screening tool in an at-home environment.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,28 An important problem in dealing with objective respiratory sounds is the comparison of the data of various investigators and correct interpretation. 50 This study shows that a snore detection system can provide an objective quantitative measure for whole-night snore patterns. Further studies are needed both to reinforce our findings by recruiting subjects from primary care clinics and by validating this screening tool in an at-home environment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in [1], M. Cavusoglu proposed another technique to detect snoring by using principle component analysis (PCA) as a feature extraction. The power spectrum of the data set was necessarily calculated to obtain the sub-band energy distribution before applying PCA.…”
Section: Snoring Detectionmentioning
confidence: 99%
“…About 50% of the adult population snores frequently. Snoring has been also reported as a risk factor for developing disorders such as ischemic brain infraction, systemic arterial hyper-arterial hypertension, coronary artery disease, and sleep disturbance [1]. Several studies have shown the relationship between snoring and OSAS, which is usually associated with loud and heavy snoring [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The passage of airflow through these airways should satisfy the equation of Bernoulli and the law of Poiseuille [1] but it moderately assures these laws, because of its particular anatomical and functional features. The UA has different segments characteristics which can be firm or collapsible depending on morphology and trophicity [2].…”
Section: Introductionmentioning
confidence: 99%